Antioxidant Properties of Egg White Hydrolysate Prevent Mercury-Induced Vascular Damage in Resistance Arteries - Escobar, Alyne Goulart; Rizzetti, Danize Aparecida; Piagette, Janaina Trindade; Peçanha, Franck Maciel; Vassallo, Dalton Valentim; Miguel, Marta; Wiggers, Giulia Alessandra (Frontiers in Physiology, 2020)
Aim: We investigated the antioxidant protective power of egg white hydrolysate (EWH) against the vascular damage induced by mercury chloride (HgCl2) exposure in resistance arteries. Methods: Male Wistar rats received for 60 days: I) intramuscular injections (i.m.) of saline and tap water by gavage – Untreated group; II) 4.6 μg/kg of HgCl2 i.m. for the first dose and subsequent doses of 0.07 μg/kg/day and tap water by gavage – HgCl2 group; III) saline i.m. and 1 g/kg/day of EWH by gavage – EWH group or IV) the combination of the HgCl2 i.m. and EWH by gavage – EWH+HgCl2 group. Blood pressure (BP) was indirectly measured and dose-response curves to acetylcholine, sodium nitroprusside, and noradrenaline were assessed in mesenteric resistance arteries (MRA), as in situ production of superoxide anion, nitric oxide (NO) release, vascular reactive oxygen species, lipid peroxidation, and antioxidant status. Results: EWH prevented the elevation in BP and the vascular dysfunction after HgCl2 exposure; restored the NO-mediated endothelial modulation and inhibited the oxidative stress and inflammatory pathways induced by HgCl2. Conclusions: EWH seems to be a useful functional food to prevent HgCl2-induced vascular toxic effects in MRA.